CHILD SEXUAL ABUSE IN INDIA: AN ANALYSIS UNDER THE NEW CRIMINAL JUSTICE JURISPRUDENCE (Maharaja Surajmal Institute Law Journal, 2025)
In the Social Fabric of Society, the child plays an important role as they are considered future nation builders. It is an important phase of human life. Children are the purest and most innocent human beings in this world but the human race has degraded themselves to such an extent that they do not hesitate to make them a target to fulfil their unlawful desires. In India, the Parliament and Judiciary have done tremendous work for the protection of the legal and human rights of children. Still, unfortunately, the children are subject to sexual exploitation directly or indirectly. India has the second-largest child population and is among the top five countries in the world that are facing the highest rate of sexual offences against children. In India every second, a child is facing emotional abuse, physical abuse, sexual abuse, or assault. In Punjab, the offences against children increased tremendously in the last few years and Child Sexual Abuse is one of them, the laws relating to child sexual abuse are very stringent in India despite that the offence is increasing day by day, resulting in an urgent need of an extensive and powerful policy as well as practical efforts to stop this menace.
Keywords: Rape; Sexual Abuse; Suicide